ANALISIS BEBAN KERJA MENTAL GURU UNTUK PERBAIKAN SISTEM PEMBELAJARAN SEKOLAH LUAR BIASA (SLB) KATEGORI B (Studi Kasus: SLB-B Karnnamanohara Yogyakarta) - Retno Widiastuti; Puji Sulistiani; V. Reza Bayu Kurniawan (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2018)
The existence of teachers is essential in educational system. Teachers have big role in students’s development. For example, students with hearing-impairment have various needs, teachers are forced not only be able to teach a number of knowledges and skills that suit with their potential and characteristic but the teacher also need to act as therapist, counsellor, and administrator as well. In doing that kind of duty. Teachers, sometimes experienced mental workload. Moreover, SLB-B Karnnamanohara Yogyakarta using full day school learning system and reflective maternal method in teaching and learning process which is the special skill in teaching is needed. Teachers sometimes suffer stress, fatigue, and financial problem. The measurenment of mental workload and identification of factors that support it was conducted to give recomendation in order to improve teaching system in this school. NASA-TLX is used as a tool to measure the mental workload. Besides, the identification of supporting factors used fishbone diagram. The result of this study reveals that the mental workload tearchers categorized in high level. In PAUD  level is 77,17; Elementery School grade 1-5 is 65; elementary school grade 4-6 is 76,17 and Junior High School is 66,33. The improvement of the system is given in order to overcome the problems  that occur in every indicators.Kata kunci:   mental workload, teacher, special education, deaf, nasa-tlx, fishbone diagram.